Dampak Korupsi Sektor Pertambangan Terhadap Kerusakan Lingkungan dan Hak Asasi Masyarakat Lokal - Sarah, Keisha Alea; Roulina, Elisabeth Julietha; Kamila, Fildza Nazhifah; Ariefandi, Nayna Carissa Putri; Gunawan, Clarissa; Mediana, Saskia; M, Mulyadi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Hh